The Influence of Service Quality on Consumer Satisfaction at Muslimah Salon and SPA - Muhammad Arif; Hendra Eka Saputra; Nur Hidayati (International Journal of Islamic Thought and Humanities, 2022)
The purpose of this research is to find out The effect of physical evidence, reliability, responsiveness, assurance and empathy (variable X) on consumer satisfaction (variable Y) at Muslimah Salon and SPA. Models used in this study is a model of causality or influence relationship. Method This research was conducted with a quantitative method approach. Subject used in this study are consumers who use the services of Muslimah Salon and SPA in Tuah Karya Village, Tampan District, Pekanbaru City, while the object is the quality of service. The population in the study was 1,656 people, while the sample is 92 people. The sampling technique used with random sampling method, while the data collection technique used is a questionnaire. In analyzing the data used multiple linear regression analysis where the process calculation using SPSS for window 23.0. Partial test results are significant influence between service quality (variable X) on customer satisfaction (variable Y) in this Muslimah Salon and SPA can be seen from the tcount of physical evidence (X1) of 4.663 > ttable of 1.662 reliability (X2) of 2.048 > ttable of 1.662 responsiveness (X3) is 2,178 and the ttable value is 1,662 guarantees (X4) is 2,060 > ttable of 1,662 empathy (X5) of 2,097 > ttable of 1,662. Coefficient value correlation of 0.860 so that it is included in the category of having a strong relationship very strong influence of service quality on customer satisfaction at the Salon and Muslimah SPA in Tuah Karya Village, Tampan District, Pekanbaru City